RANCANG BANGUN MESIN PENGOLAH LIMBAH PERTANIAN UNTUK PRODUKSI PAKAN TERNAK AWETAN DI DAERAH KERING - Endaryanta, Endaryanta; Marsudi, Ilham; Sumardjito, Sumardjito; Purwoko, Bambang Setyo Hari (Universitas Negeri Yogyakarta, 2011)
Sukorejo village, Musuk, area at Boyolali is dry farm field, whereas this field is a breeder center of milking-cow and flesh-cows. They give food to cattle by traditional method, that is the grass is cut by knife and then give directly to the animals. In wet season, this method is no problem, but in dry season this method makes a problem because there are not easy to get much grass for cattle. Consentrate mill and rice siftings are become food substitution from its food although with high price. It is really, whereas agricultural rubbish (e.g.: stick of tuberous plant, stick of papaw,